(untitled) (Psychology Travelogs, 2025)
The article examines the issue of developing metacognitive skills as a key factor in enhancing the effectiveness of programming education among higher education students. A theoretical analysis of the concepts of "metacognition" and "metacognitive skills" is conducted, outlining their role in the process of self-regulation in learning activities. The importance of developing the ability for self-regulation, self-monitoring, planning, and reflection as components of metacognitive competence is emphasized. The study analyzes scientific approaches to defining the structure of metacognitive processes and reveals the connection between their level of development and academic achievements in programming. It is demonstrated that the integration of metacognitive strategies into the learning process promotes a deeper understanding of algorithmic thinking, improved problem-solving skills, and higher academic performance. Particular attention is given to methods and tools for developing metacognitive skills in future programmers: the use of reflective journals, self-assessment, conscious planning, and error analysis. The article presents the results of a pedagogical study confirming the positive impact of well-developed metacognitive strategies on the level of mastery of programming knowledge and skills. The conclusion emphasizes the advisability of purposefully developing metacognitive competence in students as a means to enhance their success in the field of programming. Ultimately, the article highlights the need to reconsider traditional approaches to teaching programming with a focus on the development of metacognitive competence as a prerequisite for shaping autonomous, critically thinking IT professionals. The findings can be used to improve programming teaching methods, design metacognition development training, and increase students’ overall learning motivation.